PERSEPSI PENGUNJUNG TERHADAP DAYA TARIK OBJEK EKOWISATADI DESA WAAI KABUPATEN MALUKU TENGAH - Jean Tahapary; Yosevita Th. Latupapua; C. K. Pattinasarany (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
Waai village is one of the villages in central Maluku district, which has long been known for having beautiful, natural and attractive tourist attractions. The purpose of this study is to analyze visitors' perceptions of the object of ecotourism in Waai Village. The research method used is a qualitative scoring and descriptive method. Data collection techniques are done through observation, interviews, questionnaires, and literature studies. Determination of the sample is done through accidental sampling technique. The results showed that the tourist attraction of Waai Village was Aer Morea uniqueness, mountain beauty, beautiful natural scenery, waterfalls, diversity of flora and fauna as well as climatic conditions of cool temperatures, and the completeness of supporting facilities for tourists. The characteristics of tourist objects are dominated by tourists aged 15-25 years, high school education level, student / student work, gender dominated by men, many visitors from outside the area, sources of information obtained from friends / relatives, tourist destinations for recreation. The perception of visitors to the Waai Village tourist attraction is in the very satisfying category (97%) in terms of the uniqueness of the attraction, accessibility, facilities, and other supporting services as well as the security of the tourist location.